Internal Migration in Ghana : Determinants and Welfare Impacts - Ackah, Charles (2012)
Using a recently compiled dataset on migration and remittances in Ghana, this paper estimates the determinants of an individual s likelihood to be an internal migrant and the relationship between internal migration and welfare. The analysis finds that the likelihood to migrate is determined by a combination of individual (pull) and community-level (push) characteristics. The probability of migration is higher for younger and more educated individuals, but communities with higher levels of literacy, higher rates of subsidized medical care, and better access to water and sanitation are less likely to produce migrants. The analysis finds that households with migrants tend to be better off than similar households without migrants, even after controlling for the fact that households with migrants are a non-random sample of Ghanaians. However, the positive relationship is only true for households with at least one migrant in urban areas; the welfare of households with migrants exclusively in rural areas is no different from households without any migrants.